2023
DOI: 10.1021/acsphotonics.3c00568
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution In Situ Crystallization and Patterning of a CsPbBr3 Film via Femtosecond Laser Printing

Abstract: Establishing high-precision patterning technology for high-quality perovskite films is critical for practical applications requiring optoelectronic device arrays. Here, we report a femtosecond laser printing strategy to realize high-precision and high-quality patterned perovskite films by integrating in situ crystallization and patterning in one printing step. Compared with a thermal-annealed CsPbBr 3 film, the crystallization quality of a laser-printed film has been improved because of localized nucleation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Reproduced with permission. [108] Copyright 2023, American Chemical Society. f) Schematic illustration of focusing transmitted light into a 3D spot through a designed 2D perovskite flat lens with concentric rings structure; f is focal length, 𝛽 is convergence angle, and k is wave vector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [108] Copyright 2023, American Chemical Society. f) Schematic illustration of focusing transmitted light into a 3D spot through a designed 2D perovskite flat lens with concentric rings structure; f is focal length, 𝛽 is convergence angle, and k is wave vector.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al integrated in situ crystallization and patterning of CsPbBr 3 perovskite films in one fs laser printing step. [108] Laser printing can improve the crystallization quality of perovskite film owing to the localized nucleation and growth and simultaneously achieve high-resolution patterning with a minimum line width of 2 μm (Figure 8c-e). Liang et al demonstrated a fs laser regulatory focus patterning technique and fabricated an annular line of 200 nm width of perovskite film by adjusting the laser focus depths.…”
Section: Lithographymentioning
confidence: 99%